2017
DOI: 10.14569/ijacsa.2017.080820
|View full text |Cite
|
Sign up to set email alerts
|

Suitable Personality Traits for Learning Programming Subjects: A Rough-Fuzzy Model

Abstract: Abstract-Programming is a cognitive activity which requires logical reasoning to code for abstract presentation. This study aims to find out the personality traits of students who maintain the effective grades in learning programming courses such as structured programming (SP) and object oriented programming (OOP) by gender classification. Data were collected from three universities to develop, validate, and generalize the Rough-Fuzzy model. Genetic and Johnson algorithms were applied under Rough set theory's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Clustering. As a distancebased partition clustering algorithm, the K-means clustering algorithm has the advantages of simple algorithm structure, high running efficiency, and wide application range [22][23][24]. e K-means clustering algorithm is generally optimized by the objective function shown as follows:…”
Section: Basic Principles Of K-meansmentioning
confidence: 99%
“…Clustering. As a distancebased partition clustering algorithm, the K-means clustering algorithm has the advantages of simple algorithm structure, high running efficiency, and wide application range [22][23][24]. e K-means clustering algorithm is generally optimized by the objective function shown as follows:…”
Section: Basic Principles Of K-meansmentioning
confidence: 99%
“…Personality traits can foster positive employee behavior, ultimately leading to successful project outcomes (Gilal et al, 2019c;Gilal et al, 2017a). However, research has shown that personality traits such as stress tolerance, flexibility, and motivation can significantly impact the success of a software development project (Gilal et al 2019a;Gilal et al 2018;Gilal et al, 2017b). In particular, how software developers interact with each other and handle stress can have a major effect on the outcome of a project.…”
Section: Discussionmentioning
confidence: 99%
“…The three key dictionaries in this model are generic attribute dictionary, personalized attribute dictionary, and sentiment tendency dictionary. Rehman et al (2017) proposed a set of rules to identify spam reviews and combined this rule with a time series approach to identify the sentiment polarity and sentiment intensity of spam reviews. In addition, some other researchers have utilized sentiment analysis techniques in extracting feature metrics.…”
Section: Related Researchmentioning
confidence: 99%